2015
DOI: 10.1017/s0029665115000099
|View full text |Cite
|
Sign up to set email alerts
|

Is there a place for nutrition-sensitive agriculture?

Abstract: The focus of the review paper is to discuss how biotechnological innovations are opening new frontiers to mitigate nutrition in key agricultural crops with potential for large-scale health impact to people in Africa. The general objective of the Africa Biofortified Sorghum (ABS) project is to develop and deploy sorghum with enhanced pro-vitamin A to farmers and end-users in Africa to alleviate vitamin A-related micronutrient deficiency diseases. To achieve this objective the project technology development team… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…In line with our findings, a review of evidence identified lack of expertise in nutrition and poor cross-sectoral knowledge as major obstacles to jointly implement nutrition-sensitive interventions in Malawi, Nepal, and Sierra Leone [9]. Other studies also indicate limited strategic, technical, and operational capacities as a result of an insufficient number of nutrition officers, staff turnover, lack of knowledge of policy documents, inadequate training for frontline workers [17,[20][21][22], and other capacityrelated constraints [23][24][25][26].…”
Section: Discussionsupporting
confidence: 81%
“…In line with our findings, a review of evidence identified lack of expertise in nutrition and poor cross-sectoral knowledge as major obstacles to jointly implement nutrition-sensitive interventions in Malawi, Nepal, and Sierra Leone [9]. Other studies also indicate limited strategic, technical, and operational capacities as a result of an insufficient number of nutrition officers, staff turnover, lack of knowledge of policy documents, inadequate training for frontline workers [17,[20][21][22], and other capacityrelated constraints [23][24][25][26].…”
Section: Discussionsupporting
confidence: 81%
“…In Figure 3, as highlighted by Garg, M.; it can be seen that several biofortified crops, including wheat, rice, maize, potato, and tomato were obtained through the application of all three strategies listed above [2,77]. The current results in genomic biofortification are certainly useful for the development of biofortified products as a sustainable solution to the problem of "hidden hunger," to solve the lack of micronutrients, thus serving for human health and as an economic saver [77][78][79][80][81][82]. The current results in genomic biofortification are certainly useful for the development of biofortified products as a sustainable solution to the problem of "hidden hunger," to solve the lack of micronutrients, thus serving for human health and as an economic saver [77][78][79][80][81][82].…”
Section: Figurementioning
confidence: 99%
“…Rapid growth and frequent infections, which cause ineffective utilization of the vitamin, are also critical factors of VAD (Wambugu et al, 2015). The prevalence of VAD across low and middle-income countries has generally declined over time (G. A.…”
Section: Current Situation Of Vitamin a Deficiency And Coping Strategiesmentioning
confidence: 99%
“…According to a report from IRRI -Because rice is widely produced and consumed, Golden Rice has the potential to reach many people, especially those missed by current interventions‖ (Abdullah & Villegas, 2015 February 16-17). Of the 600 carotenoids found in nature, only three are important precursors of vitamin A, namely, α-carotene, β-carotene and β-cryptoxanthin (Wambugu et al, 2015). In plants, vitamin A precursors occur in the form of α, β and γ-carotenes, and xanthophyll β-cryptoxanthin.…”
Section: Invention and Development Of Golden Ricementioning
confidence: 99%
See 1 more Smart Citation